2015
DOI: 10.1590/1980-5497201500060018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de diagnóstico médico de asma em adultos brasileiros: Pesquisa Nacional de Saúde, 2013

Abstract: ABSTRACT:Objective: To estimate the prevalence of asthma medical diagnosis among the adult Brazilian population (aged ≥ 18 years). Methods: This is a cross-sectional, population-based study from the 2013 National Health Survey (NHS); it is a sampling cluster process with three stages of selection: census tracts, households, and individuals. The prevalence and 95% confidence interval for the outcome "asthma medical diagnosis" reported by the interviewed subjects were calculated, besides its distribution accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 24 publications
5
24
0
20
Order By: Relevance
“…In Brazil, more specifically, asthma affects over 6 million adults, according to the National Health Survey (PNS) of the Ministry of Health (MoH) and the Brazilian Institute of Geography and Statistics (IBGE) (4).The resulting prevalence of asthma among Brazilian adults, of 4.4%, agrees with that estimated by the World Health Survey, which included 70 countries (5). PNS also showed that 43% of the affected women and 30% of the affected men had an exacerbation, and 80% of them used an asthma medication in the 12 months prior to the survey (6).…”
Section: Introductionsupporting
confidence: 63%
“…In Brazil, more specifically, asthma affects over 6 million adults, according to the National Health Survey (PNS) of the Ministry of Health (MoH) and the Brazilian Institute of Geography and Statistics (IBGE) (4).The resulting prevalence of asthma among Brazilian adults, of 4.4%, agrees with that estimated by the World Health Survey, which included 70 countries (5). PNS also showed that 43% of the affected women and 30% of the affected men had an exacerbation, and 80% of them used an asthma medication in the 12 months prior to the survey (6).…”
Section: Introductionsupporting
confidence: 63%
“…Ainda que não exista nenhuma revisão sistemática ou metanálise sobre a epidemiologia da asma no Brasil publicada até o momento, há um bom número de estudos de âmbito nacional publicados nos últimos anos, os quais permitem uma comparação adequada com os dados deste relatório [56][57][58][59][60][61] . Desses, quatro artigos abordam objetivamente a prevalência da asma na população brasileira, sendo três conduzidos com amostras compostas por crianças e adolescentes 56,57,59 e um por indivíduos adultos 61 .…”
Section: Discussionunclassified
“…Desses, quatro artigos abordam objetivamente a prevalência da asma na população brasileira, sendo três conduzidos com amostras compostas por crianças e adolescentes 56,57,59 e um por indivíduos adultos 61 . As principais estimativas nacionais de prevalência de asma entre adolescentes são bastante consistentes entre si 56,57,59 .…”
Section: Discussionunclassified
“…[1][2][3][4][5] The southern region of Brazil, characterized by a humid subtropical climate with well-defined seasons, moderately cold winters and hot summers, 6 presents the highest prevalence of diagnosis for this condition, estimated at 5.3% of adults. 7 Among elementary school students, the prevalence of clinical symptoms has been estimated at 23.6%. 8 Among diagnosed adults, 30 to 43% report having experienced an exacerbation in the previous year and up to 16% live with important physical limitations caused by the disease.…”
Section: Introductionmentioning
confidence: 99%
“…8 Among diagnosed adults, 30 to 43% report having experienced an exacerbation in the previous year and up to 16% live with important physical limitations caused by the disease. 7 Factors associated with reduced control of asthma symptoms include the underreporting of uncontrolled asthma, underuse of recommended maintenance treatments, and lack of patient information about the disease. 9 Roman R, Lima KM, Moreira MAF, Umpierre RN, Hauser L, Rados DV, et al…”
Section: Introductionmentioning
confidence: 99%